Yoga for Arthritis: A Scoping Review - Haaz, Steffany (2010)
The aim of this article was to systematically review the existing literature on the use of yoga for persons with arthritis. We included peer-reviewed research from clinical trials (published from 1980-2010) that used yoga as an intervention for arthritis patients and reported quantitative findings. Eleven studies were identified, including four RCTs and four NRCTs. All trials were small and control groups varied. No adverse events were reported and attrition was comparable or better than typical for exercise interventions. Evidence was strongest for reduction in disease symptoms (tender/swollen joints, pain) and disability, as well as improved self-efficacy and mental health. Interventions, research methods and disease diagnoses were heterogeneous. Larger, rigorous RCTs are necessary to more effectively quantify the effects of yoga for arthritic populations